Cu/C composites with a good combination of hardness and electrical conductivity fabricated from Cu and graphite by accumulative roll-bonding. (15th November 2016) - Yao, G.C.; Mei, Q.S.; Li, J.Y.; Li, C.L.; Ma, Y.; Chen, F.; Liu, M.
Abstract: Cu/C composites were prepared from Cu and graphite by accumulative roll-bonding (ARB) up to 30 cycles ( N ) with a 50% thickness reduction per cycle at room temperature. The microstructure and properties of the Cu/C composites were investigated. Results showed that ARB can remarkably decrease the size of graphite and improve the dispersion of graphite in the Cu matrix. Moreover, significant thickness reduction (down to 5 graphene layers) of the graphite was found in the Cu/C composites fabricated by ARB. The microhardness of the Cu/C composites increases with increasing N and is 3.3 times that of pure Cu for N = 30. The electrical conductivity of the Cu/C composites decreases slightly with increasing N, with a minimum of 90% IACS for N = 30. Our study indicated that ARB can be an effective method for fabrication of Cu/C composites from Cu and graphite with a combination of hardness and electrical conductivity better than or as good as that of carbon nanotube or graphene reinforced Cu matrix composites as reported. Graphical abstract: Highlights: Cu/C composites was fabricated from Cu and graphite of by accumulative roll-bonding (ARB) up to 30 cycles at room temperature. ARB can lead to refinement, enhanced dispersion and thickness reduction of the graphite (down to 5 graphene layers). The Cu/C composite has a hardness up to 3.3 times that of Cu and an electrical conductivity higher than 90% IACS.